The Comparison of Scraping, Trichogram, and Taping Techniques for Diagnosis of Demodicosis in Dog (PERBANDINGAN TEKNIK SCRAPING, TRICHOGRAM, DAN TAPING DALAM MENDIAGNOSIS DEMODEKSOSIS PADA ANJING). - Suartha, I Nyoman; Nainggolan, Willy Moris; Sidjabat, Yekhonya Rehuel; Restiati, Ni Made (Jurnal Veteriner; Vol 19 No 1 (2018), 2018)
Demodicosis is a parasitic disease which is predilected in skin. Demodicosis in dogs may present local or general clinical symptoms. The success of demodicosis treatment is highly dependent on dog immune conditions, nutritional status, disease status, and routine treatment. The success of the treatment is also affected by the accuracy in the diagnostic technique used. The purpose of this study was to compare the three diagnostic skin examination techniques namely scraping, trichogram, and taping to diagnose cases of demodicosis. A total of 20 dog samples was taken from dog patients that came to Bali Veterinary Clinic, at Prerenan, Badung, Bali, with symptoms of itching, hair loss, skin redness, scale, and hyperpigmentation. Sampling was done by technique of scraping, trichogram, and taping. Scraping technique was done by scraping the skin, trichogram technique was done by pulling hair, and taping technique was done by attaching the tape. The result of Demodex mite isolation from the three diagnostic techniques performed showed scraping technique 5.45 ± 1.05; trichogram technique 1.10 ± 0.91; and taping technique 3.50 ± 0.83 dogs. Its Concluded that scraping technique provides the best diagnostic value for the isolation of Demodex mites compared to the other two.